The outcome of severe acute malnutrition children admitted to nutrition rehabilitation centre of a tertiary level care hospital - K., Dhanalakshmi; C., Gayathri Devi (International Journal of Contemporary Pediatrics, 2017)
Background: Malnutrition is common in paediatric age group and is responsible for high morbidity, mortality and serious long term sequelae. A nutritional therapy followed by nutritional rehabilitation is a very important aspect for these children. Optimal management of these acutely ill children and a good outcome depends on an evidence based regimen of care in the Nutritional Rehabilitation Centre (NRC). We under took this study to know the outcome of SAM children admitted to the NRC of our hospital. Methods: 736 children were enrolled in the study. Data of the children like age, sex, criteria for admission, associated complications, feeding pattern, response to therapy and their outcome were evaluated. Results: female were 371 (50.40%) and male were 365(49.5%) children. 221 (30.02%) were <6months, 231(31.38%) 6-12months, 144 (19.56%) 12months-24months and 140(19.02%) were >2 years. The weight for height of all the children were less than -3SD. 72.9% of the children had complication, diarrhoea in 28.49% and pneumonia in 35.75% were the common complications. 513 (74.55%) children showed some weight gain. The mean weight gain was 4.4 gm/kg/day. Mean duration of stay was 8.45 days. Cure rate was 81% and death rate was 6.52%. Conclusions: With a cure rate of 81%, death rate of 6.52% and defaulter rate of 12.09%, falling within the acceptable range and duration of stay 8.4 days, weight gain of 4.4g/kg/days in the lower range, management of these children in specialised feeding centre is important for faster recovery and a better weight gain.